PVDF nanofiber sensor for vibration measurement in a string - Rahul Kumar Singh (2020)
Flexible, self-powered and miniaturized sensors are extensively used in the areas of sports, soft robotics, health care and communication devices. Measurement of vibration is important for determining the mechanical properties of a structure, specifically the string tension in strings. In this work, a flexible, lightweight and self-powered sensor is developed and attached to a string to measure vibrations characteristics in strings. Electrospun poly(vinylidene) fluoride (PVDF) nanofibers are deposited on a flexible liquid crystal polymer (LCP) substrate for the development of the sensor. The electrospinning process is optimized for different needle sizes (0.34-0.84 mm) and flow rates (0.6-3 mL/h). The characterization of the sensor is done in a cantilever configuration and the test results indicate the sensor's capability to measure the frequency and strain in the required range. The comparison of the results from the developed PVDF sensor and a commercial Laser Displacement Sensor (LDS) showed good resemblance (±0.2%) and a linear voltage profile (0.2 mV/με). The sensor, upon attachment to a racket string, is able to measure single impacts and sinusoidal vibrations. The repeatability of the results on the measurement of vibrations produced by an impact hammer and a mini shaker demonstrate an exciting new application for piezoelectric sensors.